2023
DOI: 10.1111/efp.12794
|View full text |Cite
|
Sign up to set email alerts
|

Rigidoporus microporus and the white root rot disease of rubber

Abstract: The rubber tree, Hevea brasiliensis (Willd. ex A. Juss.) Mull. Arg., is one of the most economically important industrial crops, producing the milky latex which is the source of the valuable global commodity natural rubber. Natural rubber provides a source of income for rural communities, especially in Southeast Asia (Singh et al., 2021;Vongkhamheng et al., 2016). Due to the high demand globally for rubber, the area of rubber plantations worldwide increased gradually from 3 million ha in 1961 to 12 million ha … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…(Wang et al, 2023b). The type species of the genus Rigidoporus is Rigidoporus microporus (Sw.) Overeem, a widely distributed plant pathogenic species in the tropics, which can have significant economic importance in rubber, cocoa, or tea plantations (Oghenekaro et al, 2020;Saidi et al, 2023;Yuan et al, 2023). Rigidoporus ulmarius (Sowerby) Imazeki, is also a plant pathogenic polypore species has a cosmopolitan distribution (e.g., Rajchenberg and Robledo, 2013;Ryvarden and Melo, 2014;Ryvarden et al, 2022;Wang et al, 2023a).…”
Section: Introductionmentioning
confidence: 99%
“…(Wang et al, 2023b). The type species of the genus Rigidoporus is Rigidoporus microporus (Sw.) Overeem, a widely distributed plant pathogenic species in the tropics, which can have significant economic importance in rubber, cocoa, or tea plantations (Oghenekaro et al, 2020;Saidi et al, 2023;Yuan et al, 2023). Rigidoporus ulmarius (Sowerby) Imazeki, is also a plant pathogenic polypore species has a cosmopolitan distribution (e.g., Rajchenberg and Robledo, 2013;Ryvarden and Melo, 2014;Ryvarden et al, 2022;Wang et al, 2023a).…”
Section: Introductionmentioning
confidence: 99%
“…Further studies confirmed that R. microporus could cause white rot disease and primarily affected the root systems of a wide range of tree species from hardwoods, conifers to food and cash crops [10,21]. It can cause significant damage and decay in the roots, leading to the weakening and eventual death of the host tree, hence regarded economically important to African and several South East Asian countries such as Malaysia, Thailand and Philippines [21,24,25].…”
Section: Rigidoporus Microporusmentioning
confidence: 99%
“…Rigidoporus genus belongs to the order Hymenochaetales and family of Meripilaceae, contains over 40 known species [21], and commonly grow on angiosperm and gymnosperm wood [17]. Rigidoporus is phylogenetically related to Oxyporus, with the former characterised by having basidiocarps with a coloured pore surface, thick-walled encrusted hyphoid cystidia (specialised structures), and mammillate cystidioles, while the Oxyporus species are associated with light-coloured basidiocarps and thick-walled encrusted hymenial cystidia [22].…”
Section: Rigidoporus Microporusmentioning
confidence: 99%